Helping Pregnant Women and Clinicians Understand the Risk of Ondansetron for Nausea and Vomiting During Pregnancy. Issue 3 (September 2019) - Haas, D.M.
Abstract : ( JAMA . 2018;320 (23):2425–2426) Nausea and vomiting during the first trimester of pregnancy is often unresponsive to conservative treatment and commonly requires antiemetic pharmacotherapy. First line agents, as per the American College of Obstetricians and Gynecologists' treatment algorithm, are pyridoxine, alone or in combination with doxylamine. However, while the safety of pyridoxine has been well established, there remain concerns regarding potential effects of other antiemetic drugs on fetal development. In particular, the study by Huybrechts et al addressed concerns about potential associations between ondansetron, a serotonin receptor agonist and third-line agent, and fetal congenital malformations. The study found no significant associations between ondansetron and cardiac abnormalities [adjusted risk difference (aRR), −0.8; 95% confidence interval (CI), 0.92-1.06] and overall congenital anomalies. A small but significantly increased risk of oral clefts with first-trimester exposure to ondansetron was found (aRR, 1.24; 95% CI, 1.03-4.08).